The Role of Antihydrogen Formation in the Radial Transport of Antiprotons in Positron Plasmas - Michael Charlton (12th International Conference on Low Energy Antiproton Physics (LEAP2016), 2017)
Study of how antihydrogen formation (and destruction by collisions) leads to rapid radial transport of antiprotons across positron plasmas at typical plasma densities and temperatures used in experiments.